Role of endothelial cells in vascular calcification - Jiang, Han; Li, Lihua; Zhang, Lili; Zang, Guangyao; Sun, Zhen; Wang, Zhongqun (Frontiers in Cardiovascular Medicine, 2022)
Vascular calcification (VC) is active and regulated extraosseous ossification progress, which is an independent predictor of cardiovascular disease (CVD) morbidity and mortality. Endothelial cells (ECs) line the innermost layer of blood vessels and directly respond to changes in flow shear stress and blood composition. Together with vascular smooth muscle cells, ECs maintain vascular homeostasis. Increased evidence shows that ECs have irreplaceable roles in VC due to their high plasticity. Endothelial progenitor cells, oxidative stress, inflammation, autocrine and paracrine functions, mechanotransduction, endothelial-mesenchymal transition (EndMT), and other factors prompt ECs to participate in VC. EndMT is a dedifferentiation process by which ECs lose their cell lineage and acquire other cell lineages; this progress coexists in both embryonic development and CVD. EndMT is regulated by several signaling molecules and transcription factors and ultimately mediates VC via osteogenic differentiation. The specific molecular mechanism of EndMT remains unclear. Can EndMT be reversed to treat VC? To address this and other questions, this article reviews the pathogenesis and research progress of VC, expounds on the role of ECs in VC, and focuses on the regulatory factors underlying EndMT, with a view to providing new concepts for VC prevention and treatment.